Statehood tradition of the turkic period (Journal of Philosophy Culture and Political Science, 2021)
The tradition of statehood on the Kazakh land has a long history. One of the stages of the tradition of statehood, dating back to the Saka and Huns epochs, is associated with the Turkic era. The Turkic period is a historical period that stands at the origins of the medieval period of Kazakhstan. This historical period, which began with the organization of the Turkic tribes as a state, is a process that continued for several centuries. During this period, the Turkic tribes were able to create various states with common characteristics and successfully performed leading functions in the region.In this article, the author clearly shows the regularity of the formation of statehood traditions in the Turkic era and makes new conclusions. In particular, the author determined that the Turkic tribes became a political institution, emphasizing the features characteristic of the early states.At the same time, in the article, identifying the signs characteristic of early states, the author was able to motivate the main features of the statehood of the Turkic era. In the course of the article, the author seeks to fully cover the main research papers on the problem. The Turkic kaganates, created in the earliest Middle Ages, are a vivid example of statehood formed by the nomads of this historical period. The author convinces that science has a Eurocentric approach, precisely formulates its groundlessness precisely through the tradition of statehood in the Turkic era.Keywords: state, Eurocentrism, kagan, politics, management, economics, nomadic lifestyle.